APPLICATION OF THE LIGEKA_21 MODEL TO DEVELOP 21ST-CENTURY SKILLS FOR STUDENTS IN LEARNING GEOGRAPHY IN HIGH SCHOOL - Sugiyanto Sugiyanto; Singgih Prihadi; Lintang Ronggowulan (Universitas Sebelas Maret (UNS), 2023)
21st Century learning skills are essential. In the revision of the 2013 curriculum in 2017, it has been explicitly stated that 21st-century skills introduced with the term 4 C (Critical thinking and problem solving, creativity and innovation, communication skills and collaboration skills) are used as an orientation in learning at school. To improve students' 21st Century Skills in Social Studies learning, a learning model called the LIGEKA_21 was developed. The results of his research show that the use of the LIGEKA_21 model can significantly improve 21st-century skills (4C) for both students in the high school group and the middle and lower group schools. Prominent results include high enthusiasm for learning, active and creativity in producing learning outputs, posters of critical and creative teaching materials, poetry based on social studies teaching materials, high mastery of social studies knowledge, development of communication skills and skills and collaboration. The results of this good research need to be developed more broadly, not only in junior high schools but also need to be developed in senior high schools. Good learning outcomes implemented using face-to-face (offline) patterns are not necessarily suitable in the Covid-19 era, which are carried out with online learning patterns, so they must be developed or adapted based on e-learning. Based on these conditions, this research will develop an online learning pattern based on the LIGEKA 21 model, which will then be compared with the LIGEKA_21 model with face-to-face (offline) learning patterns in high school.